Desain dan Optimasi Injection Mold Sistem Slider pada Produk Stick T15 - Ni'am, Lutfi Khoirul Miftakhul; Budiyantoro, Cahyo; Rahman, Muhammad Budi Nur (Jurnal Rekayasa Mesin, 2017)
The design of injection molding is the initial process to produce a large-scale product of plastic material which heated and injected into the mold. Design of the preform mold using the plastic material polyethylene terephthalate with the construction of the slider, so that the products which was made have undercut and canâ€™t be made in the core section and cavity. The purpose of this design is to design the slider on the product preform. The software which used for this design using CATIA V5R19 and simulation software production using Autodesk Moldflow Insight 2016. The step on designing a unit injection mold in the preform includes several steps. The first step is identify the product, the calculation of the cooling and input the data calculation result to an moldflow. The second step is design construction slider and determine the mold material as well as calculating the construction mold. The third step is pour the results of the design in figure 2D. Based on the analysis results from moldflow obtained cooling optimal.i.e. the type of cooling series type 2, and if can be concluded construction of the mold said to be safe if the stress, the style and the determinationÂ  of material which occurs under the stress and style of permit.